Factors Affecting the Response of Triple-Negative Breast Cancer (TNBC) to Neoadjuvant Chemotherapy: A Meta-Analysis - Aji, Haivan Kusuma; Monty Priosodewo Soemitro (HM Publisher, 2024)
Background: Triple-negative breast cancer (TNBC) is an aggressive subtype with limited treatment options. Neoadjuvant chemotherapy (NAC) is often used to downstage tumors before surgery, but response rates vary. This meta-analysis aims to identify factors that influence TNBC’s response to NAC. Methods: PubMed, Embase, and Cochrane Library databases were searched (2018-2024) for studies evaluating factors associated with TNBC response to NAC. Data on patient demographics, tumor characteristics, NAC regimens, and response rates were extracted. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using random-effects models. Results: Twenty-three studies (n=4,512 patients) were included. Younger age (OR 1.82, 95% CI 1.35-2.46), smaller tumor size (OR 0.58, 95% CI 0.41-0.82), lower clinical stage (OR 0.39, 95% CI 0.27-0.56), and absence of lymph node involvement (OR 0.42, 95% CI 0.31-0.57) were associated with improved pathological complete response (pCR) rates. NAC regimens containing platinum agents (OR 2.15, 95% CI 1.54-2.99) and immune checkpoint inhibitors (OR 1.78, 95% CI 1.23-2.58) also showed higher pCR rates. Conclusion: This meta-analysis identified several factors associated with improved TNBC response to NAC, including younger age, smaller tumor size, lower clinical stage, absence of lymph node involvement, and use of platinum-based or immunotherapy-containing NAC regimens. These findings can inform patient selection and treatment optimization for NAC in TNBC.